Temperature and salinity profiles at 10 m depth resolution from time series station E1 in the western English Channel from 1903 to 2011 - Timothy J Smyth; Nicolas J Hardman-Mountford; Matthew Frost; James R Fishwick (PANGAEA, 2012)
Datasets contains depth profiles of temperature and salinity data extractions at 10 m depth intervals for the Western Channel Observatory long-term hydrographic series at station E1 (50 02 extquotesingleN; 4 22 extquotesingleW) in the western English Channel. The 10 m extractions have been determined from the closest depth bin measurement. They do not represent the average over a 10 m slab of the water column, but rather a slab around 0.25 m thick for the electronic measurements.